Breathing Life Flows Through Chaos: Reconfiguring the Effectiveness of Five-Finger Breathing in Mental Health First Aid - Peng, Yuxin (Anthropology of consciousness, 2026)
This article questions the moral and causal certainties attributed to the clinical assumptions of the breath of chaos. Instead of seeing chaos as an exceptional intruder that causes problems in health, I suggest that chaos underlines the changing conditions of health and it's an intrinsic part of breathing and everyday life. I discuss the five-finger breathing as a therapeutic technique to cope with the shortness of breath in panic attacks. I propose that the practice makes chaos an ineluctable prompt that evokes therapeutic anchoring, which helps with the navigation of life. Moving away from the clinical assessments, I adopt the approach of participant experience to present a medical anthropological analysis of the effectiveness of five-finger breathing as practised in a mental health recovery group in Southeast England.